Analisis Yuridis terhadap Pelanggaran Hukum Humaniter Oleh Pasukan Israel di Jalur Gaza - Pratama Alifiandi; Nabila Aulia Nurahma; Nova Romadzoni Fadzillah (Majelis: Jurnal Hukum Indonesia, 2025)
The armed conflict between Israel and Palestine, particularly in the Gaza Strip, has caused severe humanitarian impacts and raised strong allegations of violations of International Humanitarian Law (IHL). Israel’s military attacks on civilians, hospitals, and public infrastructure demonstrate breaches of the principles of distinction, proportionality, and humanity as stipulated in the 1949 Geneva Conventions and the 1977 Additional Protocol I. This study aims to analyze the forms of violations committed by Israeli forces and examine their legal accountability under international law and the International Criminal Court (ICC). The research employs a normative juridical method using statutory and case approaches, with primary legal materials from international treaties and secondary materials from academic journals and human rights reports. The findings indicate that Israel’s actions in Gaza constitute grave breaches and war crimes, as they deliberately target civilians and obstruct humanitarian assistance. This study emphasizes the urgency of enforcing international law and ensuring global accountability for perpetrators while encouraging member states of the Rome Statute to support ICC-led investigations into the ongoing violations